PENGENALAN SEJARAH ISTANA MAIMUN BERBASIS QR CODE UNTUK MEMEMPERKENALKAN KEBUDAYAAN KESULTANAN DELI - Mardiah; Andrian; Khalidy, Furqan; Amir, Saiful (Sekolah Tinggi Teknologi Dumai, 2025)
Maimun Palace is one of the historical and cultural icons of the Deli Sultanate located in Medan City, North Sumatra. However, the delivery of historical information to visitors is still conventional and less interactive. This study aims to design and implement a historical introduction system for Maimun Palace based on QR Code as a digital media to introduce the culture of the Deli Sultanate in a more modern and efficient way. The methods used include data collection through literature studies, field observations, and interviews with related sources. QR Codes placed at strategic points in the Maimun Palace area will link visitors to digital content containing historical information, architecture, cultural values, and the role of the Deli Sultanate in the development of the region. The implementation results show that the use of QR Codes can increase visitors' interest and understanding of local cultural heritage. This system also provides easy access to information and supports cultural preservation through an information technology approach.